Taxes and Financial Performance of Small-Scale Businesses in Bugujju Mukono Central Division. - Saphrah Atuhaire (Uganda Christian University, 2024)
The purpose of the study is to evaluate the relationship between taxes and financial performance of small-scale businesses in Bugujju, Mukono Central division. This was guided by the following objectives: to find out the different taxes paid by small scale business owners, to examine the impact of tax rates on financial performance of small-scale businesses and to establish the effect of tax compliance on financial performance of small-scale businesses. The study used a cross-sectional research design, which involved examining data from a population at a specific point in time. This followed a quantitative research approach. The study targeted a population of 100 small-scale enterprises, consisting of 43 retail shops, 17 hardware shops, 20 groceries, and 20 dealers in general merchandise. Therefore, the sample size was set at 80 (Krejcie and Morgan, 1970).The study employed simple random sampling, ensuring that all participants in the study population had an equal chance of being selected. Data collection involved both primary and secondary sources. For data collection, the study opted for questionnaires as the primary tool. To ensure the quality of the collected data, two key factors were addressed: the reliability and validity of the research instruments. Subsequently, the data was categorized, coded, and entered into a computer database for quantitative analysis with the use of SPSS software. The study findings underscore a high level of tax compliance among small-scale businesses, indicating adherence to various taxes and fees, including trading licenses, income tax, VAT, import duties, custom duty, service fees, and fines for infractions. However, concerns about the adverse effects of high tax rates on financial performance are prevalent among small-scale business owners. Additionally, the study emphasizes the critical importance of tax compliance for financial performance and stability. All in all, the study findings demonstrate the complex relationship between taxes and financial performance for small-scale businesses. While tax compliance is necessary for regulatory adherence and fiscal responsibility, high tax rates can pose significant challenges to profitability and growth. Based on the findings of the study, small-scale business owners should prioritize tax compliance to avoid financial distress and legal repercussions. Implementing robust internal control systems and seeking professional tax advice can help ensure accurate reporting and timely payment of taxes.